Wisata Pendidikan Agro Terintegrasi: Penyusunan Rencana Induk Desa Dawung, Karanganyar melalui Pendekatan Partisipatif - Dewi, Santy Paulla; Diah Intan Kusumo Dewi; Retno Widjajanti; Titik Ekowati; Muhammad Ghozi Al Ghifari (Warta LPM, 2024)
Based on the Spatial Plan of Karanganyar Regency, Dawung Village is mandated as an agropolitan strategic area for food security or wet agriculture. Besides, it is also a center for processing agricultural food crops and local trade. In contrast, the number of farmers decreases (0.8% per year), increasing the risk in the agricultural sector. On the other hand, this village has tourism potential, Kembang Desa, which is appointed as the leading tourist attraction. Kembang Desa was developed in 2020, and after it officially opened, it was attractive, as can be seen from the visitors number that reached 200 to 500 at the weekend. However, the COVID-19 pandemic has significantly affected the number of visitors, and the village government is facing the operational budget. This situation continues because of many new tourist attractions competitors opened. Hence, economic development and village potential require a reference as a basis for the village government in determining future policies. This community service activity aims to compile a master plan for tourism and economic development in Dawung Village through Integrated Agro Edu Tourism, which focuses on developing agro-tourism integrated with the agricultural system with an tourism education approach. The method used to compile the master plan consists of three stages: socialization to the Village government about the initial design concept. The second stage is Focus Group Discussion (FGD) activities to obtain input regarding potentials, problems, design concepts, and specific needs from partners; the third stage is master plan design finalization. The community service results in a master plan of a Dawung Village hotspot as the guidance for developing local potential so that Dawung Village can be more advanced and competitive.